Free Gingival Graft: A Versatile Technique - Lamichhane, Simant; Dawadi, Asmita; Humagain, Manoj; Bhusal, Sita (Journal of Nepalese Society of Periodontology and Oral Implantology, 2022)
Root sensitivity, caries, compromised aesthetics along with difficulty in oral hygiene maintenance are the major complications of gingival recession. Different surgical techniques for root coverage with variable success rate have been documented till date. Free gingival autograft (FGG) is an autologous technique which is in practice for more than 50 years. However, the success rate for FGG is not so convincing. This case series presents a variety of recession cases classified on Miller’s recession subtypes managed successfully to counteract gingival recession and widening the band of keratinised gingiva along with special highlights on points to be considered for its success.